Gut reactions : the science of weight gain and loss - Field, Simon (Simon Quellen) (Chicago Review Press Incorporated, 2019)
"A scientific look at weight control that explains how our bodies react to food and the environment, and how our brain affects what and how much we eat and, in turn, is affected by what we eat"--